Sintesis dan Karakterisasi Pupuk Lepas lambat Fe-Zn dari Limbah Besi, Limbah Seng, dan Cangkang Telur Ayam - Rosy Dwi Rahmawati; Sunardi (Jurnal Serambi Engineering, 2024)
The synthesis of slow-release Fe-Zn fertilizer from community waste, using iron waste, zinc waste, and chicken eggshells as raw materials, aims to transform underutilized waste into economically valuable products. The study investigates three fertilizer compositions for the ratios 1:1:1, 1:1:2, and 2:1:1 (FeSO4 : CaCO3 : ZnSO4). The synthesis process involves mixing FeSO4, CaCO3, and ZnSO4 with distilled water. After mixing, the fertilizer is dried and characterized using FTIR (Fourier Transform Infrared Spectroscopy) and SEM (Scanning Electron Microscope) - EDS (Energy Dispersive Spectroscopy). SEM analysis reveals irregularly shaped Fe-Zn slow-release fertilizers with uneven surfaces. FTIR results show similar spectral regions among the three variations. The presence of CaO is indicated by absorption bands at 709.80 cm-1, while Zn-O-H bonds appear at 1,070 cm-1. Fe-O bonds are identified at 692 cm-1